2016
DOI: 10.1111/1365-2745.12582
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary responses of invasive grass species to variation in precipitation and soil nitrogen

Abstract: Summary1. Global climate models suggest that many ecosystems will experience reduced precipitation over the next century and the consequences for invasive plant performance are largely unknown. Annual invasive species may be able to quickly evolve traits associated with drought escape or tolerance through rapid genetic changes. 2. We investigated the influence of 5 years of water and nitrogen manipulations on trait values in a southern California grassland system. Seeds from two annual grass species (Avena bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 45 publications
(93 reference statements)
1
42
0
Order By: Relevance
“…Larson and Funk () reported that diverse directions and extents of responses in root traits to watering treatments were detected both in seedlings of woody and herbaceous species. However, Nguyen et al () found no phenotypic variation in the examined root traits among water treatments. Therefore, the mechanisms underlying the diverse response patterns warrant further exploration.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Larson and Funk () reported that diverse directions and extents of responses in root traits to watering treatments were detected both in seedlings of woody and herbaceous species. However, Nguyen et al () found no phenotypic variation in the examined root traits among water treatments. Therefore, the mechanisms underlying the diverse response patterns warrant further exploration.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies exploring the intraspecific responses of root morphological and chemical traits to changing water availability have revealed that both of the hypotheses are tenable (Larson & Funk, 2016;Nguyen et al, 2016;Padilla, Miranda, Jorquera, & Pugnaire, 2009;Ryalls, Moore, Johnson, Connor, & Hiltpold, 2018). For example, Ryalls et al (2018) found that the SRL of a meadow grass (Microlaena stipoides) decreased and diameter and tissue density increased under deluge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Skroppa and Kohmann 48 demonstrated adaptation of Norway spruce ( Picea abies ) to local climatic conditions after only one generation, and Franks et al 49 found rapid evolution of flowering time in the annual Brassica rapa in response to climate change after just three generations. More recently, Nguyen et al 50 showed earlier flowering in two invasive plant species in response to selection over few generations of water manipulations, and Nowak et al 51 demonstrated adaptive evolution of the Alpine Pennycress Noccaea caerulescens after one generation of exposure to various levels of zinc contamination in the soil. Due to multiple introductions and admixtures between differentiated populations, either prior or post-introduction, invasive plants can exhibit large within-population genetic diversity 52 , This has also been found for ragweed in Europe 23,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, it is shown in Brooks et al (2004) and Brown, Mitchell, and Graham (2002) that a possible hybridization with apparent native species can lead to genetic integrity issues. The evolutionary responses of some invasive species to nitrogen and water manipulations have been studied in Nguyen et al (2016), and the main observation is that their high capability of adaptation correlates with their genetics. This heralds the response of invasive species to future climate change.…”
Section: Introductionmentioning
confidence: 99%